Role of Intrinsic Properties in Drosophila Motoneuron Recruitment During Fictive Crawling - Schaefer, Jennifer E. (American Physiological Society, 2010)
Motoneurons in most organisms conserve a division into low-threshold and high-threshold types that are responsible for generating powerful and precise movements. Drosophila 1b and 1s motoneurons may be analogous to low-threshold and high-threshold neurons, respectively, based on data obtained at the neuromuscular junction, although there is little information available on intrinsic properties or recruitment during behavior. Therefore in situ whole cell patch-clamp recordings were used to compare parameters of 1b and 1s motoneurons in Drosophila larvae. We find that resting membrane potential, voltage threshold, and delay-to-spike distinguish 1b from 1s motoneurons. The longer delay-to-spike in 1s motoneurons is a result of the shal-encoded A-type K(+) current. Functional differences between 1b and 1s motoneurons are behaviorally relevant because a higher threshold and longer delay-to-spike are observed in MNISN-1s in pairwise whole cell recordings of synaptically evoked activity during bouts of fictive locomotion.